Literasi Keuangan Digital Sebagai Pemberdayaan Sumber Daya Manusia dalam Mencegah Pinjaman Online Illegal pada Ibu-Ibu Majelis Taklim Al Hasanudin - Pusporini Palupi Jamaludin; Paringsih Paringsih; Elizabeth Tika Kristina H; Budhi Prabowo (Lembaga Pengembangan Kinerja Dosen, 2025)
The importance of implementing community service activities (PKM) in the Tri Dharma of higher education has a positive impact on the community. The title of this PKM is